Development and evaluation of live attenuated Salmonella vaccines in newly hatched duckings. Issue 42 (13th October 2015) - Tang, Tian; Gao, Qun; Barrow, Paul; Wang, Mingshu; Cheng, Anchun; Jia, Renyong; Zhu, Dekang; Chen, Shun; Liu, Mafeng; Sun, Kunfeng; Yang, Qiao; Chen, Xiaoyue
Abstract Domestic ducks remain a major source of zoonotic Salmonella enterica infections for man worldwide and approaches to protection should include vaccine-mediated immunity. With this in mind we developed several genetically defined mutants in a virulent duck Salmonella typhimurium isolate TT-1. From initial tests for virulence in day-old ducks, ΔrpoS, ΔhilA, and ΔslyA mutants retained some virulence so were not studied further. Amongst the mutants showing greater attenuation, ΔssrB, ΔphoPQ, ΔompR, and ΔclpP also showed high levels of protection when 1-day-old ducks, which were vaccinated orally, were challenged 1 week later demonstrating the capacity to protect ducks in the first few weeks of life when they are most susceptible and when the risk of infection is greatest. Immunized ducks triggered Omp-specific IgG, IgM, and IgA responses and raised IL-2 and IFN-γ levels in the serum coupled with IL-4 suppression.